Integration and classification of documents from multiple sources - Kho, William. (2013)
Knowledge lies in various sources and can be found in different format and shape. One of the greatest source of knowledge we often rely on in our daily lives is non-other than the internet. There, information is mostly encoded in unstructured text or documents. In addition, knowledge extraction from text/documents these days relies on manual entry, which is often time-consuming and laborious. In order to solve this problem, a human-like intelligent agent that is capable of reasoning and decision making is built.